1997
DOI: 10.1259/bjr.70.838.9404203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vivo cardiac function with ex vivo cardiac performance of the rat heart after thoracic irradiation.

Abstract: Comparison of in vivo cardiac function with ex vivo cardiac performance of the rat heart after thoracic irradiation Franken, N.A.P.; Camps, J.A.J.; van Ravels, F.J.M.; van der Laarse, A.; Pauwels, E.K.J.; Wondergem, J. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
1
16
1
1
Order By: Relevance
“…A variety of acute and early biochemical changes associated with morphological damage and impairment of cardiac function mediated by irradiation have been demonstrated (Prignitz et al 1976;Lauk 1987;SchultzHector et al 1992;Franken et al 1992Franken et al , 1993Franken et al , 1997Persons et al 1996). Myocardial Na + , K + -ATPase activity was reduced within 30 min after irradiation of guinea pigs (Prignitz et al 1976).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A variety of acute and early biochemical changes associated with morphological damage and impairment of cardiac function mediated by irradiation have been demonstrated (Prignitz et al 1976;Lauk 1987;SchultzHector et al 1992;Franken et al 1992Franken et al , 1993Franken et al , 1997Persons et al 1996). Myocardial Na + , K + -ATPase activity was reduced within 30 min after irradiation of guinea pigs (Prignitz et al 1976).…”
Section: Discussionmentioning
confidence: 98%
“…Clinical studies have demonstrated that patients who received mediastinal irradiation for the treatment of neoplasms frequently develop cardiovascular complications long after radiotherapy (Gomez et al 1983;Morgan et al 1985;Young et al 1990). When a large portion of the heart is located in the radiation ®eld, as in the treatment of Hodgkin's disease, a dose of up to 40 Gy in 20 fractions over a 4-week period is well tolerated, but at doses above that a rapid increase in cardiac abnormalities have been reported (Stewart et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Redistribution of perfusion to, or a compensatory expansion of, previously underused alveoli may maintain an adequate gas exchange after destruction of irradiated regions (41). Also in the case of failing cardiac function, compensatory abilities have been shown either on the level of the heart itself or on the level of regulatory mechanisms of the entire cardiovascular system (42,43). Thus, it is plausible that limited damage to each of the two organs separately would remain subclinical, but its combination will exceed compensatory abilities and translate into clinically manifest symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…After a single dose of 20 Gy, myocardial degeneration becomes apparent in rats at around 6 months post-irradiation and is preceded by a marked reduction in capillary density (11). Parallel to the development of morphological damage, hemodynamic studies reveal a marked impairment of cardiac function (12,13).…”
Section: Original Articlementioning
confidence: 99%